Creation Processes of Professional Artists and Art Students in Sculpting. (July 2021) - Puppe, Linda; Jossberger, Helen; Gruber, Hans
In some creative domains, it is easy to make performance visible. For example, musician can be observed while they perform. In other domains, such as sculpting, less is known about the creation process. The objective of the present study was to analyze how professional artists and students in sculpting differ in their perception and in their creation processes as well as how perception and creation processes are related to each other. Ten experts, 10 intermediates, and 10 novices participated. First, participants' eye movements while looking at a stimulus were recorded with a remote eye-tracker. Second, they explained which elements of the stimulus were of particular interest for creating a sculpture. Third, they had to create their own sculpture. Finally, questions were asked about their creation processes. The results showed differences between the three groups regarding the start-up period, use of the stimulus, working process, reflection of problems, and final sculptures.